How the term “white privilege” affects participation, polarization, and content in online communication - Quarles, Christopher L.; Bozarth, Lia (PLOS ONE, 2022)
The language used in online discussions affects who participates in them and how they respond, which can influence perceptions of public opinion. This study examines how the term white privilege affects these dimensions of online communication. In two lab experiments, US residents were given a chance to respond to a post asking their opinions about renaming college buildings. Using the term white privilege in the question decreased the percentage of whites who supported renaming. In addition, those whites who remained supportive when white privilege was mentioned were less likely to create an online post, while opposing whites and non-whites showed no significant difference. The term also led to more low-quality posts among both whites and non-whites. The relationship between question language and the way participants framed their responses was mediated by their support or opposition for renaming buildings. This suggests that the effects of the term white privilege on the content of people’s responses is primarily affective. Overall, mention of white privilege seems to create internet discussions that are less constructive, more polarized, and less supportive of racially progressive policies. The findings have the potential to support meaningful online conversation and reduce online polarization.